A new theoretical model accounting for film flow in unsaturated porous media. Issue 8 (19th August 2013) - Wang, Yunquan; Ma, Jinzhu; Zhang, Yali; Zhao, Menzhu; Edmunds, W. Mike
<x xml:space="preserve">Abstract</x> [1] Commonly used soil hydraulic models that account for capillary forces often do not perform well when water flow occurs in thin liquid films in unsaturated porous media. A new theoretical soil water retention curve model was formulated based on the film thickness function that accounts for matric potential. Coupling this new model with a modified Tokunaga model that considers hydraulic conductivity yields a theoretical and mathematically simple soil hydraulic model that accounts for film flow in unsaturated porous media. Inverse modeling of an evaporation experiment showed that the new model provides a good description of water flow at low water contents. The combination of van Genuchten model with the modified Tokunaga model performed best in inverse modeling; however, the fitted parameters did not describe water flow under drier conditions because of the higher hydraulic conductivity and sharper water potential gradient when the water content approached the residual water content, which caused severe overestimation of water loss. Simulation of the water dynamic in a 2 m profile using the modified Tokunaga model combined with the new theoretical soil water retention curve model provided reliable results for water changes under field conditions, including very dry conditions.